2014
DOI: 10.15185/izawol.82
|View full text |Cite
|
Sign up to set email alerts
|

The impact of migration on trade

Abstract: ProsThere is a causal positive relationship between migration and international trade. A 10% increase in the stock of immigrants can boost trade by an estimated 1.5% on average. Almost no studies have found a negative impact. Rich data with better and more immigration data than past studies yield similar results. autHOr'S MaIn MeSSaGeImmigration increases trade. The size of the impact depends on the type of sending countries, the type of commodities, the type of immigrants, and the size of the existing migran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 14 publications
(22 reference statements)
0
12
0
Order By: Relevance
“…Recent literature showed that areas affected by demand shifts experience a decrease in the total migrant population. Through various channels, the reduction of migrant workers softens the adverse effects of demand shifts on native-born employment opportunities and wages and help the local labour markets recover faster (Cadena and Kovak, 2016[56]; Monras, 2018 [57]; Basso, D'Amuri and Peri, 2019 [58]; Gálvez Iniesta, 2019 [59]; Özgüzel, 2021 [60]).…”
Section: Box 46 Does Migrant Mobility Protect Native-born Employment?mentioning
confidence: 99%
“…Recent literature showed that areas affected by demand shifts experience a decrease in the total migrant population. Through various channels, the reduction of migrant workers softens the adverse effects of demand shifts on native-born employment opportunities and wages and help the local labour markets recover faster (Cadena and Kovak, 2016[56]; Monras, 2018 [57]; Basso, D'Amuri and Peri, 2019 [58]; Gálvez Iniesta, 2019 [59]; Özgüzel, 2021 [60]).…”
Section: Box 46 Does Migrant Mobility Protect Native-born Employment?mentioning
confidence: 99%
“…Labour mobility across borders can bring economic gains in a multitude of ways. Immigrants can be a key resource for businesses, facilitate transfer of skills and knowledge across borders, spur innovation in firms by increasing diversity of ideas (Docquier, Özden and Peri, 2014;Ottaviano and Peri, 2013;Hanson and Slaughter, 2016), help establish trade relationships, thereby fostering international trade (Genç, 2014), and help nations address labour and skill shortages. This is particularly true for APEC member economies like Japan, Canada, the United States, New Zealand and Australia, where demographic transition has resulted in ageing populations (OECD, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…3 Migrants can also affect their home country [through remittances, trade (e.g., Parsons 2012;Genç 2014), investment (e.g., Kugler and Rapoport 2007;Javorcik et al 2011), funding political parties, and influencing host countries' policies regarding their home country]. However, the government is likely to be more effective and have a greater impact on residents' behavior than on migrants' behavior.…”
Section: Introductionmentioning
confidence: 99%